Purpose and Implications of Islamic Dawah - Muhammad Mumtaz, Ali (2020)
In most of the books the Purpose of Islamic Dawah is presented in a religious and traditional sense. The application of IOK/ Relevantaization demands to review our understanding of Islamic Dawah, its purpose and implications to be reviewed. Hence, this article has investigated the purpose and implications of Islamic Dawah in time space context. It is contended that the purpose of dawah is to educate people about truth and reality of life. The write and truthful understanding of life will help to achieve sustainable development in life and society.